2006
DOI: 10.1177/1468798406069799
|View full text |Cite
|
Sign up to set email alerts
|

Reading through linguistic borderlands: Latino students’ transactions with narrative texts

Abstract: This study examines the biliteracy development of a group of bilingual Latino third graders in an elementary school in the south-west USA. It focuses on the role of language in children’s reading comprehension of narrative texts in Spanish and English in a school context. The authors frame their analysis within the ‘Continua of Biliteracy’ model (Hornberger, 1989, 2003), highlighting how the youngsters drew on their linguistic resources to negotiate the contexts and contents of biliteracy. Data come from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…When Gloria Anzalduá (1987) linked ethnic identity and linguistic identity, proclaiming, "I am my language," she was taking about the language of her home and community, not the language of Cervantes. In the U.S. Southwest, Spanglish is a linguistic borderland that serves to express Mexican Americans' borderland identity (González, 2001;Martínez-Roldán & Sayer, 2006).…”
Section: Using Spanglish In Schools?mentioning
confidence: 99%
See 1 more Smart Citation
“…When Gloria Anzalduá (1987) linked ethnic identity and linguistic identity, proclaiming, "I am my language," she was taking about the language of her home and community, not the language of Cervantes. In the U.S. Southwest, Spanglish is a linguistic borderland that serves to express Mexican Americans' borderland identity (González, 2001;Martínez-Roldán & Sayer, 2006).…”
Section: Using Spanglish In Schools?mentioning
confidence: 99%
“…The children read six different picture storybooks (see Table 1) and one on one with the researcher were asked to talk about the books, or to do a retelling of the story. Although a protocol was used to see if the students could identify the main story elements, they were encouraged to develop their own interpretations of the texts and to extend their discussions of the books to connect the content to their own lives (the study is reported in Martínez-Roldán & Sayer, 2006).…”
Section: Reading With Bilingual Kidsmentioning
confidence: 99%
“…The increasing number of dual language programs throughout the United States represents the potential for a shift in language orientations from language as a problem toward language as a resource (Ruiz, ) and from subtractive toward additive bilingualism (Lambert, ). In contrast to prevailing discourses in the United States, which frame bilingual education as a compensatory program designed to bridge a temporary gap for children who enter school with limited English proficiency and are therefore unable to fully participate in school, more and more educators are beginning to consider the capacity to communicate in languages other than English as an asset to be developed in school: an academic advantage that can lead to bilingualism, biculturalism, and biliteracy (García, ; Gort, ; Hornberger & Link, ; Martínez–Roldán & Sayer, ; Palmer & Martínez, ).…”
mentioning
confidence: 99%
“…Retelling is another component reading skill assessed by IRIs. Having a biliterate identity, comprised of bi/multicultural, bi/multilingual, and bi/multiliteracy knowledge, can help bilinguals construct meaning from texts (Jiménez, 2002;Martínez-Roldán & Sayer, 2006;Pacheco, 2010). The findings reported by Dorner, Orellana, and Li-Grining (2007) explicitly linked language brokering, interpreting, and paraphrasing with bilinguals' increased ability to draw reliable propositions about the academic texts they read.…”
Section: Downloaded By [North Dakota State University] At 17:14 16 Nomentioning
confidence: 58%
“…A responsive approach to literacy instruction for bilinguals includes sheltered English (Escamilla, 2009) and systematically engages their bidialectical knowledge about literacy (Martínez-Roldán & Sayer, 2006). When bilingual education teachers systematically create learning opportunities that engage bilinguals' bidialectical knowledge about literacy, they sustain Downloaded by [North Dakota State University] at 17:14 16 November 2014 a bilingual reader's perception that reading in two languages is a unitary cognitive process.…”
Section: Responsive Literacy Instructionmentioning
confidence: 99%